1981
DOI: 10.1128/aem.41.6.1442-1453.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manual Brush Cleaning on Biomass and Community Structure of Microfouling Film Formed on Aluminum and Titanium Surfaces Exposed to Rapidly Flowing Seawater

Abstract: Metals exposed to rapidly flowing seawater are fouled by microbes that increase heat transfer resistance. In this study, results of biochemical test methods quantitatively relating the biomass and community structure of the microfouling film on aluminum and titanium to heat transfer resistance across the metal surface during three cycles of free fouling and manual brushing showed that cleaning accelerates the rate of fouling measured as the loss of heat transfer efficiency and as microfouling film biomass. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Increasing flow increases the shear forces on a biofilm and the velocity of the transport mechanisms to and from a biofilm. Together with relatively high temperatures (-25°C), this could explain why OTEC research workers report more compact, filamentous (1,13) and productive (pO-50 = 4 to 16 pLg [dry weight] cm-2 day-', depending on tube material [10]) biofilms as compared with what is reported here. An additional reason for the difference may be the difference in the material and the structure of the solid surfaces (metal versus glass).…”
Section: Discussionsupporting
confidence: 49%
“…Increasing flow increases the shear forces on a biofilm and the velocity of the transport mechanisms to and from a biofilm. Together with relatively high temperatures (-25°C), this could explain why OTEC research workers report more compact, filamentous (1,13) and productive (pO-50 = 4 to 16 pLg [dry weight] cm-2 day-', depending on tube material [10]) biofilms as compared with what is reported here. An additional reason for the difference may be the difference in the material and the structure of the solid surfaces (metal versus glass).…”
Section: Discussionsupporting
confidence: 49%
“…Indirect effects of these polymers include the stabilization of sediments and soils by the presence of invertebrate feeding tubes and microbial extracellular polysaccharide polymers (19,20,36,49). Recent evidence has indicated that microbially produced extracellu-lar polymers may be particularly important in heat transfer resistance by the microfouling community that is formed when metal surfaces are exposed to rapidly flowing seawater (33,34).…”
mentioning
confidence: 99%
“…Samples of titanium (commercial grade) and 5052 aluminum pipes were exposed to seawater that was flowing at 1.85 m/s at the Naval Coastal Systems Center, Panama City, Fla. The pipe samples were removed from the system, drained, frozen, and returned to the laboratory; the lipids were extracted; and the pipes were allowed to dry (33). The extracellular polymer was recovered by the exposure of the insides of the pipes to a suspension of 25% (wtl vol) acid-washed, 00-mesh, silicate rock chips in distilled water containing 10o chloroform in a specially constructed shaker that subjected the inside surfaces to the abrading action of the chips.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Uncontaminated subsurface aquifer sediments contain microbiota with very high levels of extracellular polysaccharides indicating poor nutrient conditions ). The microfouling community formed on metal surfaces exposed to rapidly flowing seawater shows a rapid accumulation of uronic acid containing extracellular glycocalyx as a response to mechanical or chemical countermeasures (Nickels et al 1981a;1981c;White and Benson 1984). Preliminary evidence indicates that these polymers have a role in increasing marine sediment stability (Nowell et al 1985).…”
Section: Nutritional Statusmentioning
confidence: 99%